Ball collecting and sorting robot - Ahmad Hawwari; Mohmmad khateeb (My University, 2025)
This project is considered very important because it reduces people's effort in games that contain balls. This idea came to reduce human effort, by creating a robot capable of collecting balls. The robot is capable of move on its own in an autonomous manner, and it can also be operated wirelessly. Our project detects existing ball objects and collects them to specific known point , it can be used to help Tennis and Golf players to collect balls while they are training or playing matches. The most important things to cover in this project for us is making a little car that has an arm, and collect balls then sort them based on color. In this project we will use Dc motors for the wheels, servo motor for the arm , Ultrasonic Sensor ,2 ring on the robot to put the balls , controlling robot movement and collecting balls process using Arduino, color sensor.